Dirāsat Taṣnīf al-Muʿjam al-ʿArabī: (Taḥlīl al-Manhaj al-Abjadī al-ʿĀdī fī Taṣnīf Muʿjam al-Munjid) - Moh Ismail; Fairuz Subakir Ahmad (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2015)
The study of dictionary classification is one of the branches of philology that focuses on the methods of compiling dictionaries with the aim of clarifying the meanings of words in a language. Dictionary compilation employs various classification methods that differ according to the lexicographical school adopted. These include the anagrammatic (taqlīb) school, the rhyme (qāfiyah) school, the alphabetical school, and several other lexicographical traditions. An understanding of these schools enables users to benefit more effectively from dictionaries by familiarizing themselves with the methods employed by their compilers, the principles underlying their organization, and the appropriate ways to use them. The standard alphabetical method is one of the major approaches to dictionary classification. In this method, lexical entries are arranged into sections and chapters according to the normal sequence of letters in each word. The arrangement begins with the first letter, followed by the second and third letters, without rearranging or permuting the root letters. Thus, dictionary entries are organized according to the first letter while taking into account the second and third letters in their natural order. This method has become one of the simplest and most accessible systems for learners of Arabic. Based on this background, the researchers consider the study of this method essential for students of Arabic and scholars interested in lexicography. Therefore, this article aims to describe and analyze the standard alphabetical method employed in the classification of Al-Munjid Dictionary.